Pyridinium Chlorochromate Supported on to Copper(II) Sulfate as a Rapid and Efficient Oxidizing Agent for Oxidation of Alcohols under Microwave Irradiation - Niknam, Khodabakhsh (Asian Journal of Chemistry, 2016)
A rapid and convenient method is described for oxidizing aclcohols into carbonyl compounds using pyridinium chlorochromate supported on to copper sulfate under microwave irradiation.